Development of Interactive Multimedia Based on Edutainment and Problem Solving for Magnetism Learning in Elementary School - Dhita Salsabilla Winayu; Nur Ngazizah; Ageng Triyono (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2026)
Teacher and student evaluations also revealed that the multimedia was highly practical due to its user-friendly interface, attractive design, and ability to enhance students' learning motivation. Overall, these findings confirm that the developed multimedia is appropriate for use in elementary science instruction, as it fulfills the established criteria of validity, practicality, and effectiveness. This study aimed to develop interactive multimedia based on edutainment and problem-solving approaches for magnetism learning among fifth-grade elementary school students. The research employed the ADDIE development model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The multimedia was validated by two media experts and one subject matter expert before being implemented through a limited trial involving 10 students and a field trial involving 28 students at SD Negeri Kliwonan. The findings showed that the developed multimedia achieved a validity score of 94.40%, indicating that it was highly valid for classroom use. Practicality evaluation revealed very positive responses from teachers and students, demonstrating that the multimedia was easy to operate, engaging, and capable of supporting the learning process. In addition, the effectiveness test produced an average N-Gain score of 0.841, indicating a high level of effectiveness in improving students' conceptual understanding of magnetism. These results demonstrate that the developed multimedia is valid, practical, and effective for supporting science learning in elementary schools.